Financial crises : lessons from the past, preparation for the future - Caprio, Gerard; Hanson, James A.; Litan, Robert E., 1950-; World Bank Group; Brookings Institution (Washington, D.C. : Brookings Institution Press, 2005)
"Analyzes the efficacy of attempts to recover from past crises and their lessons for the future, assesses the current state of international financial markets and examines policy options for reducing systemic vulnerability, and addresses pension system reform"--Provided by publisher.
Based on the sixth annual financial markets and development conference held Apr. 26-27, 20015 in Washington, D.C., the conference was cosponsored by the World Bank Group and the Brookings Institution.
Includes bibliographical references and index.
Keywords: Financial crises; International finance; Monetary policy; Economic policy